The axisymmetric shrink fit problem subjected to torsion - Lopes, JP; Hills, DA (Elsevier, 2020)
The problem of an elastic shaft fitted into an under-sized hole in an elastically identical body, the latter in the form of a half-space, has been studied when the assembly is subject to increasing and then subsequently reducing torque. The solution has been found as the superposition of a unilateral solution for an adhered contact pair and a set of ring dislocations along the contact interface to represent slip. The dislocations needed are prismatic (bz) and twist or screw (bθ), and by using continuous distributions of them the modified traction may be represented very effectively in a way which enables the local orthogonality requirement of slip to be followed rigorously. The residual interface tractions left when the applied torque has been completely removed are found. The whole calculation was carried out on a quasi-static basis.